PUSTAKAWAN SEBAGAI INFLUENCER LITERASI DIGITAL : ANALISIS KONTEN DI MEDIA SOSIAL - Siregar, Muhammad Ardiansyah; Rahmi, Lailatur; Fakhlina, Resty Jayanti (UIN Imam Bonjol Padang, 2025)
The advancement of information technology has transformed the way people access and consume information, with social media emerging as a new space for interaction, learning, and the dissemination of digital literacy. This article explores the strategic role of librarians as digital literacy influencers on social media platforms. Using a descriptive qualitative approach, the article highlights how librarians serve not only as information managers but also as change agents who actively share educational content, raise awareness of information literacy, and foster a critical and inclusive digital culture. The findings show that librarians who creatively and communicatively engage with social media can reach a broader audience—especially digital natives—and enhance the public image of the library profession. The article recommends enhancing librarians’ digital competencies to ensure they remain adaptive and relevant in the face of ongoing digital transformation.